Migration of Two Synthetic Phenolic Antioxidants and Their Degradation Products from Wheat Straw-Based Plastic Lunch Boxes - WANG Jinxin, LIANG Yingyin, ZHONG Huaining, HU Changying (Shipin Kexue)
A method based on gas chromatography-mass spectrometry (GC-MS) was developed for the determination of the residues of 2,4-di-tert-butylphenol (2,4-DTBP), butylated hydroxytoluene (BHT) and its derivatives 2,6-di-tert-butyl-p-benzoquinone (BHT-Q) and 3,5-di-tert-butyl-4-hydroxybenzaldehyde (BHT-CHO) and their migration to isooctane from wheat straw-based plastic lunchboxes. The effects of food handling practices such as microwaving, steaming, and refrigeration on the migration of these four substances were explored. The experimental results showed that the migration behaviors of 2,4-DTBP, BHT, BHT-Q and BHT-CHO from plant fiber-based plastic products to food simulants were mainly related to the types of food simulants, residue amounts and actual application scenarios. Repeated microwaving, cooking and freezing of straw-based plastic lunch boxes might affect (or even slightly increase) the release of some compounds, but their concentrations remained relatively low and tended to decrease with increasing number of repeated cycles, and even the migration of the compounds became negligible after several consecutive applications. BHT-Q, BHT, 2,4-DTBP, and BHT-CHO migrating from wheat straw-based plastic lunch boxes were found to be relatively safe for consumers.